Mulching with oilseed rape improving soil moisture and fertility and apple yield in orchard in semi‐arid region - Wang, Chunli; Cao, Chenhui; Qiang, Cheng; Wang, Jianping; Wang, Zhouli; Zhang, Zhi; Chen, Wenjie; Yang, Jianli (Agronomy journal, 2023)
This study was aimed to alleviate water deficiency and improve soil fertility in orchards in a semi‐arid region. The Brassica napus L. winter varieties (including the varieties V6 and V7) (V6 and V7 belong to the Brassica napus L. winter variety 1721‐1B, and Qin‐you‐7) generally had higher aboveground biological yield, lower root yield, and main root length compared to the Brassica campestris L. winter or spring varieties. By mulching root area of apple tree with aboveground part of these rape varieties in later autumn, the water contents in 0–20, 20–40, and 40–60 cm soil were enhanced or changed at following March and positively correlated with the mulching‐plant biomass. Similarly, under treatments of the V6‐I and V7‐I (V6‐I and V7‐I belong to mulching root area of apple tree with aboveground part of the variety V6 and V7) (the variety V6 and V7 mulching), and the V6‐II and V7‐II (V6‐II and V7‐II belong to mulching root area of apple tree with aboveground part of the V6 and V7 + 5% soil), the average water content in 0–150 cm soil was significantly increased by about 12%, 8%, 18%, and 15% at following spring, respectively; meanwhile, the treatment V6‐II and V7‐II induced significant increase in water contents in 0–25, 25–50, 50–75, 75–100, 100–125, and 125–150 cm soil profile; these treatments were conducted over 2 years; the available K, total N, and organic matter in 0–20 cm soil was significantly increased by 39.3%–151.8%, 10.0%–17.9%, and 22.7%–34.2%, the apple tree growth was promoted, and the fruit yield per plant was significantly enhanced by 16.9%–95.5%. In conclusion, the Brassica napus L. winter variety mulching, especially the mulching with the aboveground part of the Brassica napus L. winter variety + 5% soil, showed significant effect in improving soil moisture, soil fertility, and fruit yield in orchards in semi‐arid regions. Core Ideas The oilseed rape mulching application in orchard in later autumn increased soil water content at following spring. The enhanced soil water content was positively correlated with the biomass of mulching crops. The oilseed rape mulching application in orchards improved soil fertility and apple yield. Mulching with rape plant aboveground part + 5% soil had the highest effect in improving soil water content.